IEV (Ifosfamide, Epirubicin, VP16) Regimen as Salvage Therapy for Early Relapsed/Refractory non-Hodgkin/Hodgkin Lymphoma - Behrooz Najafi; Hossein Rahimi; Mohammadali Mashhadi; Adnan Khosravi (International Journal of Hematology-Oncology and Stem Cell Research, 2011)
Introduction: Management of early relapsed or refractory lymphoma [Hodgkin & non- Hodgkin Lymphoma (HL & NHL)] is a matter of problem, especially when hematopietic stem cell support is not available. The aim of this study was to evaluate effectiveness of IEV Regimen (Ifosfamide, Epirubicin, VP16), in lymphoma patients who are not candidate for stem cell transplantation. Because the majority of our patients are nonadequate for stem cell transplantation (refuse of this modality and economic problem). This reason leads to use of more effective treatment. This trial approved with ethic committee of medical university.Patients and Methods: Twenty four patients (16 male and 8 female) with early relapsed i.e. before 6 months of primary therapy (N= 21) or refractory lymphoma (N= 3) were entered. Of 24 patients 18 were diagnosed as NHL and 6 as HL. 10 cases were in stage II, 12 cases in stage III and 2 cases in stage IV. In an inpatient setting all of the patients received 3- 4 consecutive cycles of IEV (Ifosfamide, Epirubicin, VP16) and MESNA equal to Ifosfamide for uroprotection. Cycles were repeated every 21 days, for a total of three courses.Results: The overall response rate was 92% (50% complete response and 42% partial response). Complete response were observed in 8 with NHL and 4 with HL and partial response in 9 with NHL and 1 with HL respectively. There was no response in 8% (1 patient with NHL and another with HL). Toxicities were: grade 1 neutropenia (10%) and 4 (40%), grade 1 thrombocytopenia (20%), grade 2 anemia (40%) nausea (100%), fever in 80%, neutropenic fever in 30%, pneumonia in 20%, of patients, but the majority of patients improved over treatment. One case died from progressive disease and co infection with no response to antibiotic therapy. The major cause of drug toxicity was Ifosfamide (high dose usage and 3 days continuous IV infusion). Tolerance to the regimen was good.Conclusions: Our results revealed the efficacy of the IEV regimen as salvage therapy in primary refractory and early relapsed NHL & HL without stem cell support.